Organisation activity of St. Casimir society in Vilnius region districts - Ereminas, Gintautas (Genocidas ir rezistencija, 2022)
The publication presents the education of the Lithuanian people by the Lithuanian Society of St. Casimir in the Polish-ruled area under difficult conditions. Based on the materials of the Lithuanian Society of St. Casimir (f. 175) in the Manuscripts Department of the Wroblewski Library of the Lithuanian Academy of Sciences, this and other publications will aim to reconstruct the Society’s activities in the following voloks of Vilnius Region: Apsas, Benekainys, Dieveniškės, Marcikonys, Rimšė and others.
Keywords: Vilniaus region; polish occupation; polonisation; education; St. Casimir society